2017
DOI: 10.1093/pubmed/fdx046
|View full text |Cite
|
Sign up to set email alerts
|

Is popular radio a source of exposure to alcohol references in mid to later life? A content analysis

Abstract: Adults in the age group 55-64 may be exposed to references to alcohol that could serve to reinforce norms of consumption of alcohol and promote purchases of cheap alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…In line with previous studies (Daykin et al, 2009;Graham & Adams, 2014;Haighton et al, 2017;Noel et al, 2017), this investigation shows that spirits mentions encourage excessive intake. Some sportscasters insistently claim that the brand in question is consumed by everybody, at all times, and everywhere in the world.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies (Daykin et al, 2009;Graham & Adams, 2014;Haighton et al, 2017;Noel et al, 2017), this investigation shows that spirits mentions encourage excessive intake. Some sportscasters insistently claim that the brand in question is consumed by everybody, at all times, and everywhere in the world.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the association of alcohol consumption with improved physical performance, social success, or health, and in line with previous research (Daykin et al, 2009;Donovan et al, 2007;Haighton et al, 2017;Jones et al, 2010;Jones & Donovan, 2001;Noel et al, 2017;Pettigrew et al, 2012), this investigation has detected a predominant use of appeals connected with social success and winning. Graham & Adams (2014) describe the case of a television commentator, an ex-professional footballer, who suggested that alcohol consumption could be linked to the winning team, taking for granted the subsequent hangover.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation